TEACHING SPEAKING AND CORRECT PRONUNCIATION - Tursunaliyeva Durdona; Igamberdieva Shahnoza (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
This article is devoted to teaching spoken language skills the development of pronunciation skills in teaching English Spoken language is an interactive process of constructing meaning, which includes the production, receipt and processing of information.